Alpha-Al2Mo3O12 nanosheet as well as preparation method and application thereof

By epitaxially growing α-Al2Mo3O12 single crystal nanosheets using chemical vapor deposition (CVD) on a c-side sapphire substrate, the problems of complex and low quality of α-Al2Mo3O12 powder preparation steps in the prior art are solved, and nanosheet preparation with high orientation and extremely low thermal conductivity coefficient is achieved, which is suitable for a variety of high-performance applications.

CN119776988AActive Publication Date: 2025-04-08CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411987994.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In the prior art, α-Al2Mo3O12 is mainly synthesized by classic solid phase reaction methods. The product exists in powder form, with complex steps, low product quality and long processing time, which hinders its wide application in fuel cells, gas sensors and other fields.

Method used

The α-Al2Mo3O12 single crystal nanosheets were epitaxially grown on the c-side sapphire substrate by chemical vapor deposition (CVD). Through two heating steps, the temperature and time were controlled in the protective atmosphere to obtain α-Al2Mo3O12 nanosheets with high orientation and extremely low thermal conductivity coefficient.

Benefits of technology

The high-quality preparation of α-Al2Mo3O12 nanosheets is achieved, which reduces production costs, improves crystal quality, and can be prepared on a large scale, suitable for thermal insulation coatings or thermoelectric conversion fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776988A_ABST
    Figure CN119776988A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crystal preparation, and particularly relates to an alpha-Al2Mo3O12 nanosheet as well as a preparation method and application thereof. According to the invention, the chemical vapor deposition method is adopted to epitaxially grow the highly oriented single crystal nanosheet on the c-plane sapphire substrate, so that the crystal quality is improved, the production cost is reduced, and meanwhile, large-scale preparation can be realized. The invention also provides the nanosheet prepared by the preparation method according to the scheme. The nanosheet provided by the invention is a two-dimensional crystal composed of multiple layers of atoms, has an extremely low thermal conductivity coefficient, and is excellent in chemical property, optical property and electronic property. The variable-temperature Raman spectrum research of the system finds that the characteristic phonons have ultra-short service life, which indicates that the nanosheet disclosed by the invention has an extremely low thermal conductivity coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystal preparation, and specifically relates to an α-Al2Mo3O 12 Nanosheets and preparation methods and applications thereof. Background Art

[0002] Metal molybdates have attracted extensive attention due to their advantages such as chemical flexibility, negative thermal expansion and good thermal stability. They are widely used in fuel cell electrolytes, gas sensors, laser materials, electronics and supercapacitors. 12 It has a wide bandgap and excellent microwave dielectric properties, ε r =4.99, Q×f=49579GHz (f=14.8GHz), τ f =26ppm / ℃.

[0003] At present, α-Al2Mo3O 12 It is mainly synthesized by the classic solid-phase reaction method, and the product mainly exists in the form of powder. However, this method has complicated steps, low product quality and long processing time, which hinders the development of α-Al2Mo3O 12 application. Summary of the invention

[0004] The purpose of the present invention is to provide an α-Al2Mo3O 12 Nanosheets and preparation methods and applications thereof. The preparation method provided by the present invention has simple steps and obtains α-Al2Mo3O 12 Nanosheets have high orientation and extremely low thermal conductivity coefficient and excellent performance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides an α-Al2Mo3O 12 The method for preparing the nanosheet comprises the following steps:

[0007] The c-plane sapphire and the Mo source are subjected to a first heating and a second heating in a protective atmosphere in sequence, wherein the final temperature of the second heating is 750-800° C. and the holding time is 20-30 min to obtain the α-Al2Mo3O 12 Nanosheets.

[0008] Preferably, the Mo source is MoO3 powder; the purity of the MoO3 powder is above 99.99%.

[0009] Preferably, the distance between the c-plane sapphire and the Mo source is 3 to 9 cm; and the c-plane sapphire is placed downstream of the Mo source.

[0010] Preferably, the single dosage of the Mo source is 30 mg.

[0011] Preferably, the final temperature of the first heating is 700-720°C, the holding time is 5-10 min; the flow rate of the protective atmosphere is 10-30 cm 3 / min.

[0012] Preferably, the heating rate of the first heating is 13.75-20.5°C / min.

[0013] Preferably, preheating is performed before the first heating; the final temperature of the preheating is 280-320°C, the holding time is 10-30 min, and the heating rate is not less than 13.75°C / min; the flow rate of the protective atmosphere is 250-350 cm 3 / min.

[0014] Preferably, the heating rate of the second heating is not less than 1.3°C / min.

[0015] The present invention also provides α-Al2Mo3O obtained by the preparation method described in the above scheme 12 Nanosheets.

[0016] The present invention also provides the α-Al2Mo3O 12 Application of nanosheets in thermal insulation coatings or thermoelectric conversion.

[0017] The present invention provides an α-Al2Mo3O 12 The invention discloses a method for preparing nanosheets. The invention adopts chemical vapor deposition (CVD) to epitaxially grow highly oriented α-Al2Mo3O on a c-plane sapphire substrate. 12 Single crystal nanosheets improve crystal quality, reduce production costs, and can be prepared on a large scale.

[0018] The present invention also provides α-Al2Mo3O obtained by the preparation method described in the above scheme 12 Nanosheets. The α-Al2Mo3O 12 Nanosheets are two-dimensional crystals composed of multiple layers of atoms, with extremely low thermal conductivity and excellent chemical, optical and electronic properties. Systematic temperature-dependent Raman spectroscopy studies have found that characteristic phonons have an ultra-short lifetime (~0.12ps), indicating that α-Al2Mo3O 12 The nanosheets have extremely low thermal conductivity.

[0019] The present invention also provides the α-Al2Mo3O 12 Application of nanosheets in thermal insulation coatings or thermoelectric conversion. 12Nanosheets have extremely low thermal conductivity and are suitable for use in thermal insulation coatings or thermoelectric conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The α-Al2Mo3O provided by the present invention 12 Crystal structure diagram of nanosheets;

[0021] Figure 2 α-Al2Mo3O on c-plane sapphire 12 XPS full spectrum of nanosheets (a) and XPS fine spectra of Mo 3d, Al2p and O1s nuclear energy levels corresponding to the full spectrum (b-d);

[0022] Figure 3 Sapphire substrate and α-Al2Mo3O 12 EDS spectra of nanosheets (a and c) and α-Al2Mo3O 12 SEM image of nanosheets and corresponding EDS elemental images of Al, O and Mo (b);

[0023] Figure 4 α-Al2Mo3O 12 XRD spectrum of nanosheets;

[0024] Figure 5 To transfer to the α-Al2Mo3O 12 Nanosheet optical image (a), α-Al2Mo3O 12 Low-magnification TEM image of the nanosheet (b) and HRTEM image of the area indicated by the white box in the low-magnification TEM image (c); the inset shows the Fourier filtered image and the corresponding SAED pattern of the area indicated by the red box;

[0025] Figure 6 α-Al2Mo3O 12 Schematic diagram of CVD growth on c-plane sapphire;

[0026] Figure 7 α-Al2Mo3O of Example 1 12 Optical image of nanosheets (a), inset is α-Al2Mo3O 12 AFM image of the nanosheet; and the corresponding Raman spectrum (b);

[0027] Figure 8 α-Al2Mo3O of Example 2 12 Nanosheet optical image (a) and corresponding Raman spectrum (b);

[0028] Fig. 9The optical image of the ultrathin α-MoO3 nanosheet of Comparative Example 1 (a), the inset is the AFM image of the α-MoO3 nanosheet; and the corresponding Raman spectrum (b);

[0029] Fig.10 The photo (a) and corresponding Raman spectrum (b) of the centimeter-sized α-MoO3 nanosheets of Comparative Example 2. DETAILED DESCRIPTION

[0030] The present invention provides an α-Al2Mo3O 12 The method for preparing the nanosheet comprises the following steps:

[0031] The c-plane sapphire and the Mo source are subjected to a first heating and a second heating in a protective atmosphere in sequence to obtain the α-Al2Mo3O 12 Nanosheets.

[0032] In the present invention, the c-plane sapphire is preferably cleaned and then dried before use; the cleaning reagents are preferably acetone, isopropanol and hydrogen peroxide; the cleaning method is preferably ultrasonic cleaning; the drying is preferably blow-drying; and the blow-drying equipment is preferably a nitrogen gun.

[0033] In the present invention, the Mo source is preferably MoO3 powder; the purity of the MoO3 powder is preferably above 99.99%; the MoO3 powder is preferably purchased from Aladdin. The present invention uses MoO3 powder as the Mo source, and the c-plane sapphire substrate is used as both the Al source and the substrate to epitaxially grow α-Al2Mo3O on its surface. 12 Nanosheets.

[0034] In the present invention, the distance between the c-plane sapphire and the Mo source is preferably 3 to 9 cm, more preferably 6 to 8 cm; the c-plane sapphire is preferably placed downstream of the Mo source (such as Figure 6 The present invention regulates the distance between MoO3 powder and substrate to adjust the α-Al2Mo3O 12 Growth of nanosheets.

[0035] In the present invention, the single dosage of the Mo source is preferably 30 mg.

[0036] In the present invention, the protective atmosphere is preferably nitrogen. In the present invention, nitrogen is introduced as a carrier gas and a protective gas.

[0037] In the present invention, the first heating device is preferably a tube furnace and a quartz ark; the quartz ark is preferably placed in the center of the quartz tube of the tube furnace; the inner diameter of the quartz tube is preferably 2 cm, and the length is preferably 40 cm; the final temperature of the first heating is preferably 700-720°C, more preferably 710°C, and the insulation time is preferably 5-10 min, more preferably 7-8 min; the flow rate of the protective atmosphere is preferably 10-30 cm 3 / min, more preferably 15 to 25 cm 3 / min, more preferably 20cm 3 / min. The present invention uses a quartz ark to hold the raw materials. The present invention can control the temperature in the tube furnace and the crystal growth time to adjust the α-Al2Mo3O 12 Growth of nanosheets.

[0038] In the present invention, the heating rate of the first heating is preferably 13.75-20.5° C. / min, more preferably 16-18° C. / min.

[0039] In the present invention, preheating is preferably performed before the first heating; the final temperature of the preheating is preferably 280-320°C, more preferably 300-310°C, the holding time is preferably 10-30min, more preferably 15-25min, the heating rate is preferably not less than 13.75°C / min, more preferably 13.75-60°C / min, further preferably 20-40°C / min; the flow rate of the protective atmosphere is preferably 250-350cm 3 / min, more preferably 280 to 320 cm 3 / min. The present invention removes the air in the quartz tube by preheating.

[0040] In the present invention, the second heating device is preferably a tube furnace and a quartz ark; the quartz ark is preferably placed in the center of the quartz tube of the tube furnace; the inner diameter of the quartz tube is preferably 2 cm, and the length is preferably 40 cm; the final temperature of the second heating is preferably 750-800°C, more preferably 770-790°C, and the insulation time is preferably 20-30 min, more preferably 24-27 min; the flow rate of the protective atmosphere is preferably 10-30 cm 3 / min, more preferably 15 to 22 cm 3 / min. The present invention uses a quartz ark to hold the raw materials. The present invention can control the temperature in the tube furnace and the crystal growth time to adjust the α-Al2Mo3O 12 Growth of nanosheets.

[0041] In the present invention, the heating rate of the second heating is preferably not less than 1.3° C. / min, more preferably 2 to 18° C. / min, and further preferably 5 to 10° C. / min.

[0042] In the present invention, the second heating preferably includes post-treatment; the post-treatment includes system cooling, tail gas treatment and / or exhaust.

[0043] In the present invention, the temperature reduction is preferably natural cooling; and the final temperature of the natural cooling is preferably room temperature.

[0044] In the present invention, the tail gas treatment reagent is preferably alkali solution. The present invention ensures stable air pressure and prevents alkali solution from flowing back through exhaust.

[0045] The present invention also provides α-Al2Mo3O obtained by the preparation method described in the above scheme 12 Nanosheets.

[0046] The α-Al2Mo3O 12 Nanosheets, monoclinic Al2Mo3O 12 (α-Al2Mo3O 12 ), belongs to the P21 / a (No.14) space group, and the lattice parameters are a=1.549nm, b=0.911nm, c=1.800nm, α=γ=90°, β=125.30°.

[0047] The α-Al2Mo3O 12 The crystal structure of the nanosheets is Figure 1 As shown, Al atoms and Mo atoms are surrounded by 6 oxygen atoms and 4 oxygen atoms, respectively, forming AlO6 octahedron and MoO4 tetrahedron, and the AlO6 and MoO4 polyhedrons are connected by O atoms sharing corners to form a framework structure.

[0048] The present invention also provides the α-Al2Mo3O 12 Application of nanosheets in thermal insulation coatings or thermoelectric conversion.

[0049] The α-Al2Mo3O 12 Nanosheets have extremely low thermal conductivity and are suitable for use in thermal insulation coatings or thermoelectric conversion.

[0050] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0051] Example 1

[0052] In this embodiment, α-Al2Mo3O is epitaxially grown on a c-plane sapphire substrate.12 Nanosheets, the device used is as Figure 6 As shown, the specific steps are:

[0053] (1) First, use a glass cutter to cut the c-plane sapphire substrate along its [11-20] crystal direction. First, carve the periphery of the substrate with a knife, and then use tweezers to pry it apart. The substrate will break along the crystal direction and be cut into long strips. During the cutting process, a large amount of fine debris will fall on the substrate. The substrate is cleaned in an ultrasonic oscillator with deionized water, acetone, isopropyl alcohol, and hydrogen peroxide, respectively. Each cleaning process takes 15 minutes. Use a nitrogen gun to blow dry the substrate for later use.

[0054] (2) 30 mg of MoO3 powder was weighed and placed in a quartz ark. The quartz ark containing MoO3 powder and c-plane sapphire substrate was placed in the center of a quartz tube (inner diameter 2 cm, length 40 cm). The quartz tube containing MoO3 powder was then placed in the inner heating zone, and the pre-cleaned c-plane sapphire substrate was placed 5 cm downstream of the MoO3 powder. The tube furnace was then sealed and N2 was passed as the carrier gas and protective gas.

[0055] (3) At 300 cm 3 At a N2 flow rate of 1.54 W / min, the heating zone was heated from room temperature to 300°C in 20 min and kept at this temperature for 20 min. Subsequently, the N2 flow rate was adjusted to 20 cm / min. 3 / min, the heating zone was heated to 710℃ in 20min and kept for 5min, then heated to 750℃ in 30min and kept for 20min to obtain α-Al2Mo3O 12 Nanosheets. The tubular furnace is naturally cooled to room temperature; the tail gas from the tubular furnace is connected to the graduated straw through a silicone tube, inserted into a glass washing bottle, sealed with a rubber stopper, and the washing bottle is filled with alkali solution to absorb the tail gas, and the outlet of the washing bottle is connected to the exhaust fan system through a silicone tube.

[0056] Example 2

[0057] The preparation method of this embodiment is the same as that of embodiment 1, except that the growth time and temperature of the second heating are 30 min and 800° C. respectively; the product characterization results are shown in FIG. Figure 8 As shown. Figure 8 It can be seen that a single-oriented α-Al2Mo3O is epitaxially grown on the surface of the c-plane sapphire substrate. 12 nanosheets, indicating that increasing the nucleation density by appropriately increasing the growth time and temperature may be beneficial to breaking the energy merger and thus promoting the growth of α-Al2Mo3O 12 Highly oriented growth of nanosheets.

[0058] Comparative Example 1

[0059] The preparation method of this comparative example is the same as that of Example 1, except that the c-plane sapphire substrate is placed 10 cm downstream of the MoO3 powder; the product characterization results are shown in Fig. 9 As shown. Fig. 9 It can be seen that except for a small amount of square α-Al2Mo3O 12 In addition to the nanosheets, most of the c-plane sapphire substrate surface is covered by irregular α-MoO3 nanosheets with a thickness of ~5.6 nm, indicating that the larger distance between the c-plane sapphire substrate and the MoO3 powder, that is, the lower MoO3 concentration, may limit the bonding reaction and make the α-Al2Mo3O 12 Nanosheets are difficult to form, while MoO3 precursor molecules are adsorbed on the surface of c-plane sapphire substrate to form α-MoO3 nanosheets.

[0060] Comparative Example 2

[0061] The preparation method of this comparative example is the same as that of Example 1, except that the c-plane sapphire substrate is placed 20 cm downstream of the MoO3 powder; the product characterization results are shown in Fig.10 As shown. Fig.10 It can be seen that due to the obvious temperature difference with the external environment, the temperature at the quartz tube nozzle drops sharply, forming a large degree of supercooling, which serves as the driving force for the condensation of MoO3, depositing a large number of centimeter-sized α-MoO3 flakes at the quartz tube nozzle, while no α-Al2Mo3O is deposited on the c-plane sapphire substrate. 12 and α-MoO3 nanosheets.

[0062] Test Example 1

[0063] The α-Al2Mo3O prepared in Example 1 was characterized by optical microscopy (OM), Raman, atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), energy dispersive X-ray spectrometer (EDS), X-ray diffraction (XRD) and transmission electron microscopy. 12 Characterization of nanosheets.

[0064] The α-Al2Mo3O prepared in Example 1 12 The nanosheets were tested by XPS and EDS, and the results are as follows Figure 2 shown. Figure 2 (a) is α-Al2Mo3O 12 The full XPS spectrum of the nanosheet shows four main elements: O, C, Mo and Al. The C1s peak at 284.80 eV is a signal of amorphous carbon. This peak is usually used to calibrate the peak position of the XPS spectrum through charge compensation. Its source is generally derived from amorphous C contamination during sample transfer. O, Mo and Al come from the nanosheet and the substrate. Figure 2(b-d) show the XPS fine spectra of Mo 3d, Al 2p and O1s core energy levels corresponding to the full spectrum. The peaks at 74.28 and 531.46 eV correspond to Al 2p and O1s energy levels, respectively. There is a pair of peaks at 233.15 and 236.30 eV, which are consistent with the Mo in MoO3. 6+ 3D 5 / 2 and 3D 3 / 2 The energy levels are consistent, indicating that Mo in the product exists in the +6 valence form; the XPS spectrum confirms that the chemical composition of the nanosheets is composed of three elements: O, Mo and Al.

[0065] In order to determine the amount of each component of O, Mo and Al, α-Al2Mo3O 12 The nanosheets were subjected to EDS measurement, and the results are shown in Figure 3 shown. Figure 3 (a) is the EDS spectrum of the sapphire substrate, showing an atomic ratio of Al:O = 41.3:58.7≈2:3. Since the EDS measurement depth far exceeds the sample thickness, and the Al and O signals mainly come from the sapphire substrate; Figure 3 From the EDS spectrum in (b), we can see that the atomic contents of O, Al, and Mo are 60.1%, 37.4%, and 2.5%, respectively. By subtracting the contribution of Al and O in a ratio of 2:3, the amounts of O, Mo, and Al in the nanosheets are 1.6:2.5:9.9≈2:3:12, confirming that the nanosheets are α-Al2Mo3O 12 ; Figure 3 The EDS elemental map in (c) reveals that α-Al2Mo3O 12 Homogeneous distribution of Mo, O, and Al in the nanosheets.

[0066] For the α-Al2Mo3O 12 The nanosheets were subjected to XRD spectrum analysis, and the results were as follows Figure 4 shown. Figure 4 α-Al2Mo3O on c-plane sapphire substrate 12 The XRD spectrum of the nanosheets shows four diffraction peaks at 2θ = 14.18°, 28.51°, 43.33° and 58.93°, corresponding to α-Al2Mo3O 12 According to the diffraction angle and the Bragg diffraction theorem, the spacing between the (100) crystal planes of the nanosheet is 1.25 nm, which is similar to that of α-Al2Mo3O 12 (ICDD-JCPDS-PDFNo.01084-1652) The lattice spacing in the (100) crystal plane is consistent, indicating that the nanosheets epitaxially grown on the c-plane sapphire substrate are α-Al2Mo3O 12 .

[0067] To further verify the 12 The atomic structure of the nanosheets, α-Al2Mo3O 12 The nanosheets were transferred to a copper mesh (eg Figure 5 HRTEM and SAED measurements were performed, and the results are shown in Figure 5 As shown in b and c. Figure 5 The corresponding low-magnification TEM image is shown in b, where the nanosheets are in the shape of truncated rectangles; the missing parts are all isosceles right triangles; Figure 5 The middle c shows Figure 5 HRTEM image of the white square area in (b) with atomic resolution; Figure 5 The corresponding SAED pattern is inserted in the upper right corner of (b), showing rectangular symmetry and confirming that the

[010] and

[001] directions correspond to the α-Al2Mo3O 12 The right-angled edges of the nanosheets are at an angle of 45°; the Fourier filter image of the red square highlighted area inserted in the lower right corner shows that the lattice spacing is ~0.45nm and 0.91nm, corresponding to α-Al2Mo3O 12 (020) and α-Al2Mo3O 12 (002) interplanar spacing, so the α-Al2Mo3O epitaxially grown on the c-plane sapphire substrate 12 The crystal structure of the nanosheets was further confirmed.

[0068] The α-Al2Mo3O prepared in Example 1 12 The nanosheets were analyzed by AFM and Raman spectroscopy. Figure 7 As shown. Figure 7 It can be seen that α-Al2Mo3O was epitaxially grown on the c-plane sapphire substrate. 12 Nanosheets.

[0069] It can be seen from the above examples that the preparation method provided by the present invention can epitaxially grow highly oriented α-Al2Mo3O on a c-plane sapphire substrate. 12 Single crystal nanosheets improve crystal quality, reduce production costs, and can be prepared on a large scale.

[0070] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A kind of α-Al2Mo3O 12 The method for preparing a nanosheet is characterized in that: The following steps are involved: The c-plane sapphire and the Mo source are subjected to a first heating and a second heating in a protective atmosphere, wherein the final temperature of the second heating is 750-800° C. and the holding time is 20-30 min to obtain the α-Al2Mo3O 12 Nanosheets.

2. The preparation method according to claim 1, characterized in that: The Mo source is MoO3 powder; the purity of the MoO3 powder is above 99.99%.

3. The preparation method according to claim 1 or 2, characterized in that: The distance between the c-plane sapphire and the Mo source is 3-9 cm; the c-plane sapphire is placed downstream of the Mo source.

4. The preparation method according to claim 1 or 2, characterized in that: The single dosage of the Mo source is 30 mg.

5. The preparation method according to claim 1, characterized in that: The final temperature of the first heating is 700-720°C, and the holding time is 5-10 minutes; the flow rate of the protective atmosphere is 10-30 cm 3 / min.

6. The preparation method according to claim 1 or 5, characterized in that: The heating rate of the first heating is 13.75-20.5°C / min.

7. The preparation method according to claim 1, characterized in that: The first heating is preceded by preheating; the final temperature of the preheating is 280-320°C, the holding time is 10-30 min, and the heating rate is not less than 13.75°C / min; the flow rate of the protective atmosphere is 250-350 cm 3 / min.

8. The preparation method according to claim 1 or 7, characterized in that: The heating rate of the second heating is not less than 1.3°C / min.

9. α-Al2Mo3O obtained by the preparation method according to any one of claims 1 to 8 12 Nanosheets.

10. α-Al2Mo3O according to claim 9 12 Application of nanosheets in thermal insulation coatings or thermoelectric conversion.

Citation Information

Patent Citations

  • Molybdenum disulfide@molybdenum disulfide core-shell nano rod growing along <010> crystal orientation and preparation method thereof

    CN109868505A

  • Preparation method and application of wafer-level absolute single-layer transition metal chalcogenide

    CN113088922A

  • Molybdenum trioxide two-dimensional crystal material and preparation method and application thereof

    CN118792735A